Pooh's neighborhood - Zoehfeld, Kathleen Weidner; Cuddy, Robbin; Milne, A. A. (Alan Alexander), 1882-1956. ([United States] : Grolier Books, 1998)
Winnie the Pooh takes a tour of the Hundred Acre Wood on his way to make a neighborly visit to Piglet.
"Based on the Pooh Stories by A.A. Milne"--T.p. verso.
Keywords: Winnie-the-Pooh (Fictitious character) -- Juvenile fiction; Neighborliness -- Juvenile fiction; Winnie-the-Pooh (Fictitious character) -- Fiction; Neighborliness -- Fiction; Neighborhood -- Fiction; Neighbors -- Fiction; Teddy bears -- Fiction; Toys -- Fiction